Moving toward Universal Coverage of Social Health Insurance in Vietnam - Aparnaa Somanathan (2022)
The objective of this report is to assess the implementation of Vietnam SHI and provide options for moving towards UC. This is a joint assessment with development partners, World Health Organization, United Nations Children's Fund (Unicef) and Rockefeller Foundation